Catalytic hydrogenation of alkyne with planar tetracoordinate carbon in CAl3MgH2¯ system - Malhan, Abdul Hamid; Thirumoorthy, Krishnan (Frontiers in Chemistry, 2025)
The present work reports the catalytic function of the planar tetracoordinate carbon (ptC) molecule, CAl3MgH2¯, for the first time. The hydrogenation of alkyne and alkene using CAl3MgH2¯ as a catalyst has been computationally examined through density functional theory calculations. Various quantum chemical tools are employed to analyze the reaction pathways systematically. The study also highlights that the reaction is favourable in the gas phase as compared to the solvent phase, suggesting the practical feasibility of using the CAl3MgH2− catalyst in the industry. Intrinsic reaction coordinate analysis confirms that the transition states are truly connected to the local minima. Furthermore, natural atomic charges and elongated bond lengths confirm the heterolytic cleavage of H2. Non-covalent interaction analysis illustrates the significant role of van der Waals interactions in coordinating reactants and stabilizing products. This study highlights the potential of the ptC molecule CAl3MgH2− as a catalyst for hydrogenation reactions, eventually opening up new avenues for planar hypercoordinate and main-group metal-based catalysts.